Semiótica del discurso político - Dávalos Carrasco, Cristal Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
The topic that we will approach is inscribed in two disciplines: in the political philosophy and in the semiotic. Both, in turn, they can be included in the environment of the philosophy of the culture. The idea of an analysis semiotic of the speech and in particular of the speech politician is more or less recent that has been approached by diverse disciplines as the anthropology (in the origins of the language) the linguistics (discursive analysis) and, for supposition, the semiology. In this last authors like Roland stand out Barthes, Paolo Fabbri, Bernard Lamizet, Patrick Charaudeau and Mexican Gilberto Giménez, for to only mention to some. The word is the one that allows that the culture and the human society are established, and for rising he/she makes possible the existence of the political order. Therefore the analysis of the one language can be inserted in a semiotic of the culture as well as in the problem of the political thing, particularly him with respect to the signs that the political speech emits, the acts by means of which is represented, recognize and he/she interprets, that is to say, their exhibition and show, as well as their interpretation and influence in the individual behavior and collective, the premeditation and seduction that he/she keeps all political speech in permanent association .positive or negative with the power.

El tema que abordaremos está inscrito en dos disciplinas: en la filosofía política y en la semiótica. Ambas, a su vez, pueden ser englobadas en el ámbito de la filosofía de la cultura. La idea de un análisis semiótico del discurso y en particular del discurso político es más o menos reciente, que ha sido abordada por diversas disciplinas como la antropología (en los orígenes del lenguaje) la lingüística (análisis discursivo) y, por supuesto, la semiología. En ésta última sobresalen autores como Roland Barthes, Paolo Fabbri, Bernard Lamizet, Patrick Charaudeau y el mexicano Gilberto Giménez, por mencionar sólo a algunos. La palabra es la que permite que se instauren la cultura y la sociedad humana, y por consiguiente hace posible la existencia del orden político. Por lo tanto el análisis del lenguaje puede ser insertado en una semiótica de la cultura así como en la problemática de lo político, particularmente lo referente a los signos que el discurso político emite, los actos mediante los cuales se representa, reconoce e interpreta, es decir, su exhibición y espectáculo, así como su interpretación e influencia en la conducta individual y colectiva, la intencionalidad y seducción que guarda todo discurso político en permanente asociación —positiva o negativa— con el poder.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2007-0007; Disciplina; Política; Discurso; Semiosis; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/39